ANALISIS KEBUTUHAN SEKOLAH SIAGA BENCANA GEMPA DAN TSUNAMI PADA SD NEGERI KAJHU KECAMATAN BAITUSSALAM ACEH BESAR - Samudra .; Nasaruddin .; Indra . (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2017)
This study aims to determine the needs of facilities and infrastructure, and the level of preparedness of SD Negeri Kajhu Aceh Besar to the earthquake and tsunami disaster. This research is descriptive qualitative and quantitative research. The study was conducted on the entire school community consisting of principals, vice principals, heads of administration, staff teachers, school carers, cafeteria attendants, and students. The sample was taken as many as 73 people. The data were collected by observation, interview, and distribution of questionnaires distributed to the school community using the percentage formula. The results show the availability of facilities and infrastructure of the school community in the face of the earthquake and tsunami disaster, there are several items that must be completed, such as availability of logistics reserves, clear evacuation direction signs and easy to understand by the school community, and the availability of evacuation places in the Kajhu Elementary School Aceh Besar. For the level of school community preparedness, analyzed by 4 key indicators of preparedness, it can be described that community preparedness of SD Negeri Kajhu Aceh Besar to earthquake and tsunami disasters is good category, with the average value of preparedness variable is 67